Physical Activity, Inactivity and Sleep in Individuals with Hypertrophic Cardiomyopathy - Charman, Sarah J; Blain, Alasdair P; Okwose, Nduka C; Fuller, Amy S; Alyahya, Alaa I; Hallsworth, Kate; Eggett, Christopher; Luke, Peter; Bailey, Kristian; MacGowan, Guy A; Jakovljevic, Djordje G (International Journal of Sports Medicine, 2023)
Physical activity presents an important cornerstone in the management and care of individuals with hypertrophic cardiomyopathy (HCM). Twenty-one individuals with HCM (age: 52±15 years old, body mass index (BMI): 30±7 kg/m2) completed 7-day monitoring using wrist-worn triaxial accelerometers (GENEActiv, ActivInsights Ltd, UK) and were compared to age and sex-matched healthy controls (age: 51±14 years old, BMI: 25±4 kg/m2). For individuals with HCM, clinical parameters (left atrial diameter and volume, peak oxygen consumption, NTproBNP and Minnesota Living with Heart Failure (MLHF)) were correlated with accelerometry. After adjusting for BMI, individuals with HCM spent less time in moderate-vigorous physical activity (MVPA) (86 (55–138) vs. 140 (121–149) minutes/day, p<0.05) compared to healthy controls. Individuals with HCM engaged in fewer MVPA-5 min (6 (2–15) vs. 27 (23–37) minutes/day, p<0.01) and MVPA-10 min bouts (9 (0–19) vs. 35 (17–54) minutes/day, p<0.01) versus healthy controls. For HCM only, peak oxygen consumption was correlated with MVPA (r=0.60, p<0.01) and MVPA-5 min bouts (r=0.47, p<0.05). MLHF score was correlated with sleep duration (r=0.45, p<0.05). Individuals with HCM should be encouraged to engage in moderate-intensity physical activity bouts and reduce prolonged periods of inactivity in order to potentially improve exercise tolerance and reduce disease burden.
Keywords: myopathy; cardiology; physical activity; sleep